Docetaxel induces Bcl-2- and pro-apoptotic caspase-independent death of human prostate cancer DU145 cells - OGURA, TAKEHARU (Int J Oncol, 2016)
Docetaxel is a useful chemotherapeutic agent for the first-line treatment of hormone-refractory prostate cancer. Abnormal expression of Bcl-2 is commonly found in cancer cells, which increases their anti-apoptotic potency and chemo-resistance. We investigated the effects of Bcl-2 expression status on the susceptibility of DU145 cells, an androgen-independent human prostate cancer cell line, to docetaxel and other anticancer agents. A panel of Bcl-2-expressing DU145 cell lines was established. Bcl-2 expression levels were unrelated to the susceptibility of DU145 cells to docetaxel. The sensitivity of DU145 cells to cisplatin fluctuated, and the sensitivity to tumor necrosis factor (TNF)-α was decreased by Bcl-2 overexpression. In a xenograft mouse model, overexpression of Bcl-2 drastically decreased the sensitivity of DU145 cells to cisplatin and TNF-α; however, there was no change in the response to docetaxel. Fluorescent microscopy revealed that Bcl-2-overexpression had no effect on the docetaxel-induced death of DU145 cells, but significantly decreased DU145 cell death induced by cisplatin or TNF-α. Interestingly, docetaxel hardly induced caspase-3/7 activation in control or Bcl-2-overexpressing DU145 cells, but did at a low level in LNCaP cells, another prostate cancer cell line. Moreover, in contrast to LNCaP cells, the reduced viabilities of docetaxel-treated control and Bcl-2-overexpressing DU145 cells were not restored by the addition of either a Bid inhibitor or a panel of pro-apoptotic caspase inhibitors. These findings indicate that the antitumor effects of docetaxel on DU145 cells are independent of both Bcl-2 and pro-apoptotic caspases.